Confidence in pedagogical efficacy of m-learning among teachers from the kingdom of Saudi Arabia - Althuwaybi, Ali Sahal (Kansas State University, 2021)
The purpose of the research was to evaluate confidence in the pedagogical efficacy of M-Learning among teachers from the Kingdom of Saudi Arabia based on an initiative learning program known as Khebrat that focuses on enriching learning experiences in universities abroad, such as Kansas State University. The research instrument included a survey consisting of a 22-item questionnaire using the Likert scale (1-4), and data analysis measured significance of the results. Data was collected with the aid of Survey Monkey, an online platform. In order to strive for accuracy, each teacher that participated in the study could either agree or disagree with the offered statement, and no neutral answers were included. Examining the efficacy of M-Learning, descriptive statistics and Cronbach’s Alpha reliability were chosen to measure the sample population average responses mean, standard deviation, variance, correlation and internal consistency between the items. The Cronbach's Alpha value obtained is r > 0.994, a high score of reliability in participants' responses. However, the pedagogical effectiveness of mobile learning remains to be further explored by developing the impact of M-learning on the consistency of the learning process.
Keywords: Education; Pedagogical efficacy; Professional learning; Confidence; TeachersM-learning